(untitled) (Revista educación, investigación, innovación y transferencia, 2021)
This paper analyses the effect of social networks on cognitive and affective empathy. Specifically in the population of young university students of education and psychology. To this end, a quantitative research was carried out using a correlational design based on the use of psychometric questionnaires. After an exhaustive analysis of the data, it was found that there is an addictive use of social networks at the same time as there are difficulties in empathy. It is also observed that this situation has been aggravated as a consequence of the current global pandemic situation. However, it is observed that as age increases and social relationships improve, there are fewer difficulties in the cognitive component of empathy. Finally, it is found that despite the strong scientific evidence from previous studies linking social network addiction with anxiety, the present study argues for its non-significance. This circumstance is even more common in the male sex, with the female sex being more sensitive to this situation.